Penilaian Kinerja Koperasi Serba Usaha Karyawan Pemerintah Kota Semarang Tahun 2011 - Setyowati, Margaret; Indarti, Iin (Jurnal Kajian Akuntansi dan Bisnis, 2012)
Cooperatives should be able to turn a profit and improve membersâswelfare, and also should be able to provide the best services to consumers. MultipurposeCooperative of Semarang City Government Employees had a problem where membershave questioned the performance problems due to dissatisfaction with the profit received.This study evaluated the performance of cooperatives with the cooperative health analyzedusing ratios that are based on Regulation of Indonesian Minister for Cooperatives, Smalland Medium Enterprises No. 14/Per/M.KUKM/XII/2009, to assess aspects of capital, assetquality, management, efficiency, liquidity, independence and growth, and aspects of thecooperative identity. Assessment of the value system with a value of 0 to 100, total score ofthe seven aspects are used to establish the cooperativeâs predicate. Data for calculation ofratios derived from financial statements of cooperatives in 2011, for the managementaspects used questionnaires that filled in by the Chairman of the Board of Cooperative.Assessed from the aspect capital performance is quite good performance with the score of8.40 from the total score of 15, from the aspect of asset quality performance with goodperformance from the score of 21.25 from the total score of 25, from the aspect ofperformance management is good cooperation with the score 11.50 from the total score of15, from the aspect of the performance efficiency of cooperation both with the score 7 fromthe total score of 10, from the liquidity aspect of performance is quite good cooperationwith the score of 8.75 from the total score of 15, from the aspect of self-reliance andgrowth of cooperatives good performance with the score 7 from the total score of 10, fromthe aspect of co-operative identity both with the Cooperative performance score of 8.50from the total score of 10. Cooperative performance scores in 2011 based on thecalculation from total aspects, obtained a total score of 72.40 from the total score of 100,with the title quite well. This suggests that the cooperative performance is good enough butnot optimal in empowering its capital.Keywords : Assessment, Performance, Cooperative